THE EFFECT OF HUMAN DEVELOPMENT ON THE LOGISTICS EFFICIENCY OF THE COUNTRIES - Emrah Akdamar (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
This study has two main aims. The first aim of the study is to determine the logistics efficiency of the countries. For this purpose, the logistics efficiency of 160 countries was measured by Data Envelopment Analysis, using six sub-indicators of the Logistics Performance Index (LPI). The second aim of the study is to investigate how the logistics efficiency of countries is affected by human development classes and indicators. For this purpose, the Kruskal Wallis H test and Multiple Linear Regression analysis were used. The findings show that countries in the Very High Human Development class have higher efficiency scores than other countries. The logistics efficiency of Sub-Saharan African Countries, which have a low level of Human Development, was found to be low. In addition, HDI sub-indicators explain logistics efficiency by 67.8%. GNP per capita and Expected Years of Schooling have a significant impact on logistics efficiency. The findings show that achieving a meaningful improvement in logistics depends on catching a leap in the economy through R&D, innovation, and high technology and considering long-term education programs.